Sun International : moving to 'We will rock you', (part B) - Viedge, Conrad (SAGE Business Cases., 2018)
It was June 2018, and group chief strategy and operations officer, Rob Collins, had just received the 'Sun Way' from consulting firm Blueprints, a series of measurements and principles for Sun International, a chain of hotels and casinos, to improve performance. Sun International had contracted Blueprints to help integrate and embed its new business philosophy, as well as to re-engage its staff in the business. As Collins read the scores, he thought about the Blueprints process and how it had evolved since he last used it at Tsogo Sun Gaming in 2005. At that time, it had been a cultural intervention spearheaded and run by the human resources department, but now it embraced the entire business philosophy of the organisation and was run by operations. The scores from Sun City were not that different from what Collins had expected. As he wondered how effective the process would be in restoring the 'We Will Rock You' era of the 1980s, Collins pondered what his role should be in ensuring that the Blueprints intervention really did bring about change at Sun International.